Exploring the impact of online reading habits on English language achievement among EFL leaners - Yentri Anggeraini; Nopa Yusnilita (Concept : Community Concern for English Pedagogy and Teaching, 2025)
In the digital era, online reading integrates text, visuals, and audio, making the Internet a dynamic source of information for learners. This study explores the impact of online reading habits on English language achievement among Indonesian EFL learners. A correlational research design was employed, involving 138 eleventh-grade students selected through convenience sampling. Data were collected using a validated and reliable online reading habits questionnaire and English achievement test. The findings reveal a statistically significant correlation between students’ online reading habits and their English scores. While students actively engage in online reading during English learning, the results indicate that frequent exposure to online texts alone does not directly translate into substantial improvement in English achievement. These findings suggest the importance of guiding learners to engage critically with online content to maximize its potential for language development. Keywords: online reading habits; English language achievement; EFL learners; digital reading